Sharia-Based Accountability in Sharia Cooperatives (Case Study at PT. Mega Central Finance Lhokseumawe City) - Muammar Khaddafi; Lestari Lestari; Chessy Luviana Helmi; Putri Zahratul Jannah; Nailan Saadah Ritonga (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
The aim of this article is sharia-based accountability. The type of research used is library research or literature review. Library research is a form of research carried out by collecting various references which are the main sources for this article published in journals and other written articles. The results of this research show the sharia-based accountability carried out by MCF Syariah. There are three types of accountability carried out, namely accountability towards God, humans and nature. The activities carried out by the company are based on the worship of God.